2021
DOI: 10.1039/d1ra00834j
|View full text |Cite
|
Sign up to set email alerts
|

Metal free C-3 chalcogenation (sulfenylation and selenylation) of 4H-pyrido[1,2-a]pyrimidin-4-ones

Abstract: We have discovered an unprecedented metal-free route for the direct C-3 chalcogenation of various 4H-pyrido[1,2-a]pyrimidin-4-ones under mild conditions in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Methods for pyridopyrimidin-4-ones selenylation with diselenides were also developed. For this purpose, I 2 /K 2 S 2 O 8 system [215] and PIFA [216] are applied. Various aromatic and aliphatic diselenides efficiently react with pyridopyrimidin-4-ones, containing electron-donating Quinazolinones 191 are sulfenylated with disulfides 192 with the use of Cu(OAc) 2 and p-benzoquinone (Scheme 83).…”
Section: Reactions With the Formation Of Cà S And Cà Se Bondsmentioning
confidence: 99%
“…Methods for pyridopyrimidin-4-ones selenylation with diselenides were also developed. For this purpose, I 2 /K 2 S 2 O 8 system [215] and PIFA [216] are applied. Various aromatic and aliphatic diselenides efficiently react with pyridopyrimidin-4-ones, containing electron-donating Quinazolinones 191 are sulfenylated with disulfides 192 with the use of Cu(OAc) 2 and p-benzoquinone (Scheme 83).…”
Section: Reactions With the Formation Of Cà S And Cà Se Bondsmentioning
confidence: 99%
“…was also consumed. At the same time, they found that excellent yields could be also obtained by using iodine molecule (I 2 ) instead of hypervalent iodine reagent (PIFA) (Scheme 2, c), [13] however, excessive oxidant (K 2 S 2 O 8 ) consumption remains another problem. Although C 3 ‐selenylated 4H‐pyrido[1,2‐ a ]pyrimidin‐4‐ones were synthesized in moderate to good yields via above selenation reaction, these methods all require excessive consumption of diphenyldiselenide and use a lot of iodine reagents or oxidants, which do not meet the requirements of atom‐economy.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-coupling reaction of halogenated or boronated alkenes and selenium reagents, e.g., ArSeSeAr and KSeCN, offers another alternative, which primarily affords the disubstituted selenium-containing olefins. In recent years, C­(sp 2 )–H bond selenization has provided another method for obtaining selenoethylene . However, the stereoselective synthesis of acyclic tetrasubstituted vinyl selenides is still challenging (Scheme b).…”
mentioning
confidence: 99%